1984
DOI: 10.1113/jphysiol.1984.sp015307
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic response of the rat to plasma concentrations of arginine vasopressin within the physiological range.

Abstract: SUMMARY1. The relationship of plasma vasopressin concentrations in the physiological range to renal electrolyte excretion was investigated.2. Unanaesthetized rats, when normally hydrated, were found to have a plasma vasopressin concentration of 113 + 015 ,su./ml. 16 h water deprivation raised this to 1P98+0-21 ,su./ml.3. Inactin-anaesthetized rats infused with 0 45 % NaCl had a plasma vasopressin concentration of 1 19 + 0418 su./ml. Administration of synthetic arginine vasopressin at 6 and 24 ,uu./min raised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
2
38
3
Order By: Relevance
“…[2][3][4][5][6][7][8][9] The dose-response curve performed in this study shows that this effect occurred only for high doses (15 and 50 g/kg BW) that probably increased P AVP levels distinctly above those involved in water conservation, even after 24 h of water deprivation, as judged here by the urinary AVP data (Table 2). With lower doses (0.1 and 1 g/kg BW), likely corresponding to the range of usual osmotic stimuli, Figure 4.…”
Section: V1ar Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9] The dose-response curve performed in this study shows that this effect occurred only for high doses (15 and 50 g/kg BW) that probably increased P AVP levels distinctly above those involved in water conservation, even after 24 h of water deprivation, as judged here by the urinary AVP data (Table 2). With lower doses (0.1 and 1 g/kg BW), likely corresponding to the range of usual osmotic stimuli, Figure 4.…”
Section: V1ar Effectsmentioning
confidence: 99%
“…In the isolated microperfused CD, V2R activation increases sodium transport, 1 an effect that should reduce sodium excretion in vivo; however, in a number of studies, AVP infusion in animals and humans has been shown to induce an increase in sodium excretion. [2][3][4][5][6][7][8][9] It is usually assumed that AVP might contribute to some forms of hypertension by its vasoconstrictive effects, but an increase in sodium excretion, if it occurred in normal life, should more likely contribute to lower BP.…”
mentioning
confidence: 99%
“…Acutely hypophysectomized rats exhibit marked alteration in renal function, characterized by avid retention of sodium (Lichardus & Ponec, 1973;Balment, Brimble, Forsling & Musabayane, 1984). This has been claimed to result from the loss of posterior pituitary factors (Lichardus & Ponec, 1973) but Balment, Brimble, Forsling & Musabayane (1986) were unable to fully restore sodium excretion by administration of neurohypophysial hormone to produce plasma vasopressin and oxytocin levels within the physiological range.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that vasopressin has a natriuretic action at physiological concentrations (Balment et al, 1984), which can be inhibited by V 1 receptor antagonism (Musabayane et al, 1997). Acute chloroquine administration under conditions of volume expansion and euvolaemia increased plasma vasopressin concentrations, as well as increasing Na ϩ excretion (Musabayane et al, 1996).…”
Section: Nitric Oxide Mediates Some Chloroquine Actions 159mentioning
confidence: 99%